Is Closed Communication a Major Hindrance in an Enterprise Resource Planning Implementation? A Case Study of an Indonesian Family-Owned Company - Hartijasti, Yanki; Septian, Arry (Makara Human Behavior Studies in Asia, 2015)
The high risk of failure associated with the implementation of enterprise resource planning (ERP) system relates to resistance among employees by rejecting or sabotaging the system. Communication has been identified as a critical success factor on ERP implementation in several studies, whereas, many others do not depict any relation at all. The current study, however, argues that communication regarding the benefits of ERP system is the most critical success factor for the accomplishment of ERP implementation in family-owned company in Indonesia. Empirical data from 116 ERP users were examined by using logistic regression, which reveals that communication has significant negative effect on ERP implementation. It means the more company practices closed communication, the lesser success of ERP implementation will be achieved. Findings show that closed communication leads to poor coordination between departments which reduces the speed of problem solving in the field and causes ERP implementation in PT ABC to not be fully utilized.